Comparação da diversidade microbiana intestinal em larvas do campo e laboratório do bicudo da cana-de-açúcar, Sphenophorus levis (Coleoptera, Cucurlionidae) - Rinke, Raquel (2009)
The sugarcane weevil, Sphenophorus levis, is an important pest in sugarcane culture in São Paulo state, Brazil. To complete its life cycle, S. levis may depends on microorganisms that inhabit its intestinal tract and play an important key in the insect physiology and nutrition. In this study we report the characterization of the intestinal microbiota from population of insect larvae from field and laboratory. Analysis of 16S rDNA sequences revealed a total of fourteen genera, one group from Candidatus category and two uncultivable groups represented by Alfa-Proteobacteria, Beta-Proteobacteria, Gamma-Proteobacteria, Firmicutes and Bacteroidetes phylum. Microorganisms isolated through culture-dependent methods were classified according morphological parameters and using 16S rDNA molecular marker. In addition to bacteria, four filamentous fungi were isolated. It was observed a slightly higher bacterial diversity in field than in laboratory according to Shannon index (Field H'= 3,36; Laboratory H'= 3,26). It is also our objective in this work to search for microorganisms capable to degrade cellulose, an important event in the insect attack. From the cultivable microorganisms, five genera of bacteria and two filamentous fungi presented cellulolytic activity. This is the first study about S. levis microbiota which may contribute to understand the interaction plant-pathogen and also be useful for future development of new strategies for control of S. levis in sugarcane cultivation.